RELATIONSHIP BETWEEN JUVENILE DELINQUENCY AND PARENTS’ BACKGROUND IN MAIDUGURI METROPOLITAN, BORNO STATE, NIGERIA - Mburza, Ali; Aliyu, Mustapha Gambo (Sokoto Educational Review, 2020)
The study was a correlation designed to examine the relationship between juvenile delinquency and parents’ background in Maiduguri Metropolitan, Borno State, Nigeria. One research question and six hypotheses were answered and tested in the study. The target population of the study consists of all the 450 juvenile delinquents who were remanded in the government remand home ‘Tandari’ Maiduguri between 2005 and 2008. The researchers used all the 450 juveniles hence there was no need for sampling. The data on the research question was analyzed using descriptive statistics of percentages and rank ordering while those generated from the hypotheses were analyzed using Chi square which were estimated at 0.05 level of significance. The findings revealed five (stealing, sexual offences, truancy, drug abuse and fighting) delinquent behaviours engaged in by the children. The study also revealed that there exist significant relationship between parents’ income, marital status, education, occupation, home location and child rearing practices and juvenile delinquency. Based on these findings, it was recommended that parents should pay adequate attention to their children in terms of their activities, what they possess and movies and films they watch. While the parents themselves should endeavour to keep their marriage intact and be flexible in the way they handle the children.